Phytoplankton succession in intensive marine shrimp culture ponds treated with a commercial bacterial product - Yusoff, F M; M. S, Zubaidah; Matias, H B; Kwan, T S (Wiley, 2002)
Succession of phytoplankton dominance was studied in shrimp culture ponds treated with commercial bacterial products. Diatoms were dominant and the cyanobacteria were absent in both treated and control ponds at the beginning of the culture period. After 34 days, the diatoms significantly decreased whereas cyanobacteria increased in both ponds. Chlorophyll a increased from a mean of 35.56 mg m−3 in the first phase to 186.00 mg m−3 in the final phase, and from 42.12 mg m−3 to 242.81 mg m−3 in the treated and control ponds respectively. Cyanobacteria were significantly higher in the control compared with the treated ponds during the final phase of the culture. Algal bioassay showed that the addition of nitrogen either alone or with silica to pond water significantly increased the specific growth rate of Chaetoceros calcitrans. The specific growth rate of Oscillatoria sp. significantly increased when a combination of nitrogen, phosphorus and carbon was added to the pond water. Addition of silica seemed to depress the growth rate of Oscillatoria sp. Nutrient enrichment should be minimized and the supply of nitrogen and silica should be adequate for promoting the growth of beneficial phytoplankton in aquaculture systems.